Coarse‐Grained Refractory Composite Castables Based on Alumina and Niobium. Issue 8 (14th May 2022) - Zienert, Tilo; Endler, Dirk; Hubálková, Jana; Gehre, Patrick; Eusterholz, Michael; Boll, Torben; Heilmaier, Martin; Günay, Gökhan; Weidner, Anja; Biermann, Horst; Kraft, Bastian; Wagner, Susanne; et al.
Abstract : Niobium‐alumina composite aggregates with 60 vol% metal content and with particle sizes up to 3150 μm are produced using castable technology followed by sintering, and a crushing and sieving process. X‐Ray diffraction (XRD) analysis reveals phase separation during crushing as the niobium:corundum volume ratios is between 37:57 and 64:31 among the 4 produced aggregate classes 0–45, 45–500, 500–1000, and 1000–3150 μm. The synthesized aggregates are used to produce coarse‐grained refractory composites in a second casting and sintering step. The fine‐ and coarse‐grained material shows porosities between 32% and 36% with a determined cold modulus of rupture of 20 and 12 MPa, and E‐moduli of 37 and 46 GPa, respectively. The synthesized fine‐grained composites reached true strain values between 0.08 at 1100 °C and 0.18 at 1500 °C and the coarse‐grained ones values between 0.02 and 0.09. The electrical conductivity for the fine‐grained and the coarse‐grained material is 448 ± 66 and 111 ± 25  S cm −1, respectively. Abstract : Alumina‐niobium refractory composites with a metal content of 60 vol% are produced using castable technology. The sintered material is then crushed and sieved to obtain refractory composite aggregates, which are then used to produce coarse‐grained composite castables. The material is chemically and mechanically characterised and its electrical conductivity is determined.